Randomized Pilot Trial Measuring Knowledge Acquisition of Opioid Education in Emergency Department Patients using a Novel Media Platform. Issue 1 (January 2018) - Chakravarthy, Bharath; Somasundaram, Shashank; Mogi, Jennifer; Burns, Roshan; Hoonpongsimanont, Wirachin; Wiechmann, Warren; Lotfipour, Shahram
Background: The number of active opioid analgesic prescriptions has risen steadily, causing increases in nonmedical opioid use, addiction, and overdose. Insufficient focus on patient discharge instructions has contributed to lack of patient awareness regarding dangers of opioids. This study examines whether an educational Khan Academy–style animation discharge instruction on the dangers and safe usage of opioid analgesics elicits higher knowledge acquisition than current standard of care. Additionally, it measures the feasibility of implementing this video discharge instruction in the emergency department (ED). Methods: Fifty-two English-speaking patients aged 18 years or older receiving an opioid prescription were enrolled in this study. Patients were randomized into 2 groups. The standard of care group received verbal instruction and an informational sheet, whereas the video animation group received a 6-minute video on proper usage of opioids in addition to standard of care. Video content was sourced fromsamhsa.gov and administered within the ED prior to discharge. Both groups received a 26-question test regarding the dangers and safe usage of opioids immediately after education. An unpaired t test compared knowledge acquisition between the 2 groups. Results: Fifty-four patients were approached, 52 patients enrolled; 27 in the standard group and 25 in the animation group. The standard of care group averaged 65% knowledge acquisition (16.8/26 correct), whereas the animation group averaged 82% acquisition (21.2/26 correct). The video animation significantly increased patient knowledge acquisition about opioid medications' risks and proper usage and disposal ( P = .001). Conclusion: It can be concluded that medical knowledge acquisition is improved in the video animation group compared with the current standard of care ( P = .001). It can also be concluded that it is feasible to implement a novel media platform to educate patients receiving opioid analgesics in the ED (96.1%).